Method for releasing chemical species included in metal-organic framework, polymer gel and method for producing same
Patent Information
- Application Number
- JP2020200945
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-03
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2040-12-03
Smart Images

Figure 0007640987000005 
Figure 0007640987000006 
Figure 0007640987000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for releasing a chemical species encapsulated in a metal-organic framework, and to a polymer gel having a metal-organic framework as a cross-linking point and covalently bonded thereto, in particular, a polymer gel having a metal-organic framework encapsulating a chemical species as a cross-linking point and covalently bonded thereto.Furthermore, the present invention relates to a method for producing such a polymer gel. [Background technology]
[0002] In recent years, metal-organic frameworks (also called porous coordination polymers) have been attracting attention as adsorbents for gases, ions, etc. In addition, composites that can be molded while maintaining the performance of such metal-organic frameworks have been proposed in the past (for example, see Patent Document 1 shown below).
[0003] Incidentally, as a method for desorbing a gas from a metal-organic framework that adsorbs the gas, there is usually a method of lowering the atmospheric pressure of the metal-organic framework below the pressure during adsorption (hereinafter, this may be referred to as a "reduced pressure desorption method"). However, there are very few application fields of metal-organic frameworks to which such a reduced pressure desorption method can be applied.
[0004] In view of this situation, attempts have been made to expand the fields of application of metal-organic frameworks by designing them so that gases, ions, and the like are released from the metal-organic frameworks when they are irradiated with light or heated (see, for example, Non-Patent Documents 1 and 2 shown below). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 012373 [Non-patent literature]
[0006] [Non-Patent Document 1] Matthew.RH et al., “Dynamic photo-switching in metal-organic frameworks as a route to low-energy carbon dioxide capture and release”, Angew. Chem. Int. Ed., 2013 Mar. 25, 52(13), 3695-3698 [Non-Patent Document 2] Sada, K. et al., “Metal-organic framework tethering PNIPAM for ON-OFF controlled release in solution”, Chem. Commun., 2015, 51, 8614-8617 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to further expand the application fields of the technology for adsorption and desorption of gases and the like using a metal-organic framework. [Means for solving the problem]
[0008] In the method according to the first aspect of the present invention, a mechanical external force is applied to a polymer gel having a crosslinking point of a metal-organic framework that encapsulates a chemical species, thereby releasing the chemical species to the outside of the metal-organic framework. The metal-organic framework is also called a porous coordination polymer. Note that the term "encapsulation" is synonymous with terms such as "contain," "adsorption," and "storage." The mechanical external force may be any force that can distort the metal structure, such as a compressive force, a tensile force, or a shear force. The chemical species may be, for example, an ion, an atom, an atomic group, a molecule, or a compound. The ion may include not only an atomic ion but also a molecular ion.
[0009] As far as the inventors of the present application know, the method of releasing chemical species to the outside of the metal-organic framework located at the crosslinking points of the polymer gel by applying a mechanical external force to the polymer gel as described above has not been proposed so far, and therefore this method can further expand the application field of the technology of adsorption and desorption of chemical species by the metal-organic framework.
[0010] In the polymer gel according to the second aspect of the present invention, the metal organic framework is covalently bonded as the crosslinking points.
[0011] The inventors of the present application have found that by applying a mechanical external force to such a polymer gel, chemical species can be released outside the metal-organic framework. As far as the inventors of the present application know, such a finding has never been shown before. Therefore, such a polymer gel can further expand the application field of the technology of adsorption and desorption of chemical species by the metal-organic framework.
[0012] A polymer gel according to a third aspect of the present invention is the polymer gel according to the second aspect, in which the metal organic framework encapsulates a chemical species.
[0013] Therefore, the chemical species can be released by applying an external mechanical force to the polymer gel.
[0014] A method for producing a polymer gel according to a fourth aspect of the present invention includes a functional group introduction step and a gelation step. In the functional group introduction step, a first functional group-containing metal organic framework is prepared by introducing a plurality of first functional groups into the metal organic framework. The introduction of the first functional group is preferably performed using a first functional group-containing compound having a functional group capable of covalently bonding to an organic ligand in the metal organic framework. In the gelation step, a second functional group of a polymer having a plurality of second functional groups capable of reacting with the first functional group is reacted with the first functional group to form a covalent bond, thereby obtaining a polymer gel. [Brief description of the drawings]
[0015] [Figure 1] 1 is a graph showing the pressure dependence of carbon dioxide adsorption / desorption of Zn(AzDC)(BPE)0.5. [Diagram 2] 2 is a graph showing the viscoelastic behavior of the polymer gel according to Example 1. [Diagram 3] FIG. 2 is a schematic diagram showing the content of a carbon dioxide release experiment from a polymer gel carried out in Example 1. [Figure 4] 1 is a graph showing the amount of carbon dioxide released from Zn(AzDC)(BPE)0.5 derived units when a weight is placed on the polymer gel of Example 1. [Diagram 5] FIG. 2 is a schematic diagram showing the content of another carbon dioxide release experiment from a polymer gel carried out in Example 1. [Figure 6] 1 is a graph showing the amount of change in absorbance of an aqueous solution of basic red versus the number of compressions when the polymer gel according to Example 1 and the polymer gel according to Comparative Example 1 are compressed. [Figure 7] 1 is a graph showing the amount of change in pH of an aqueous solution of Basic Red 5 with respect to compressive stress when the polymer gel of Example 1 and the polymer gel of Comparative Example 1 are compressed in the aqueous solution of Basic Red 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] <Method for releasing chemical species encapsulated in metal-organic frameworks> The method according to the embodiment of the present invention is a method for releasing chemical species to the outside of the metal-organic framework by applying a mechanical external force to a polymer gel having a metal-organic framework that encapsulates chemical species as a crosslinking point.
[0017] It should be noted that the term "encapsulation" is synonymous with terms such as containment, adsorption, and storage.
[0018] The "external mechanical force" referred to here may be any force, such as a compressive force, a tensile force, or a shear force, as long as it is a force capable of applying distortion to the metal structure via the polymer chain.
[0019] The "chemical species" referred to here may be, for example, an ion, an atom, an atomic group, a molecule, or a compound. The ion may include not only an atomic ion but also a molecular ion. The "chemical species" referred to here may be in a gaseous state, a liquid state, or a solid state at normal pressure. However, when the chemical species is in a liquid state or a solid state, it is preferable that the chemical species is dissolved in the liquid constituting the polymer gel. When the chemical species is a gas, the chemical species is not particularly limited, and examples thereof include inorganic gases such as carbon monoxide, carbon dioxide, oxygen, nitrogen, nitrous oxide, ammonia, hydrogen, arsine, nitric oxide, hydrogen chloride, chlorine, germane, phosphorus pentafluoride, boron trichloride, nitrogen trifluoride, boron trifluoride, phosphorus trifluoride, dichlorosilane, diborane, silane, stibine, hydrogen selenide, hydrogen telluride, nitrogen dioxide, phosphine, silicon tetrafluoride, hydrogen sulfide, and sulfur hexafluoride, fluorocarbons, and the like. Examples of the isocyanate include rare gases such as carbons, helium, neon, argon, krypton, and xenon, alkanes such as methane, ethane, propane, butane, pentane, hexane, heptane, and octane, alkenes such as ethylene, propylene, butenes, pentenes, and hexenes, alkynes such as acetylene, aromatic compounds such as benzene, toluene, and xylenes, cycloalkanes, alkyl halides, ethers, alcohols, amines, epoxy compounds, and carbonyl compounds.
[0020] <Polymer gel structure> The metal organic framework is also called a porous coordination polymer. The metal organic framework that can be used in the embodiment of the present invention is not particularly limited as long as it has a function of encapsulating chemical species and a function of releasing the chemical species by deformation (via the polymer chain in the polymer gel). Meanwhile, the metal organic framework is formed from metal ions and organic ligands. In the embodiment of the present invention, the organic ligand has a functional group for introducing a functional group into the metal organic framework.
[0021] Here, the metal ion is, for example, Mg 2+ , Ca 2+ , Sr 2+,Bar 2+ 、Sc 3+ 、Y 3+ ,Tea 4+ 、Zr 4+ 、Hf 4+ 、V 4+ 、V 3+ 、V 2+ 、Nb 3+ ,Pitch 3+ 、Cr 3+ 、Mo 3+ 、W 3+ 、Mn 3+ 、Mn 2+ 、Re 3+ 、Re 2+ 、Fe 3+ 、Fe 2+ 、Ru 3+ 、Ru 2+ ,Home 3+ ,Home 2+ 、Co 3+ 、Co 2+ 、Rh 2+ 、Rh + 、Ir 2+ 、Ir + ,Knee 2+ ,Knee + 、Pd 2+ 、Pd + 、Pt 2+ 、Pt + 、Cu 2+ 、Cu + 、Ag + 、Au + 、Zn 2+ 、Cd 2+ 、Hg 2+ 、Al 3+ 、Ga 3+ ,His 3+ 、Tl 3+ ,See 4+ ,See 2+ 、Ge 4+ 、Ge 2+ 、Sn 4+ 、Sn 2+ 、Pb 4+ 、Pb 2+ ,As 5+ ,As 3+ ,As + 、Sb 5+ 、Sb 3+ 、Sb + ,Be 5+ ,Be 3+, Bi + etc.
[0022] In addition, examples of the organic ligand include aromatic compounds, aliphatic compounds, alicyclic compounds, heteroaromatic compounds, heterocyclic compounds, etc., having multiple functional groups capable of coordinating with metal ions. As the organic ligand, aromatic compounds, aliphatic compounds, alicyclic compounds, heteroaromatic compounds, and heterocyclic compounds having one functional group capable of coordinating with metal ions may be used in combination with aromatic compounds, aliphatic compounds, alicyclic compounds, heteroaromatic compounds, and heterocyclic compounds having multiple functional groups capable of coordinating with metal ions described above. In addition, in the organic ligand, it is preferable that 1 to 5 functional groups capable of coordinating with metal ions are present for one aromatic compound, aliphatic compound, alicyclic compound, heteroaromatic compound, and heterocyclic compound, more preferably 2 to 4 functional groups are present, and even more preferably 2 to 3 functional groups are present. Such functional groups include glycidyl groups, carboxyl groups, carboxylic anhydride groups, hydroxyl groups, thiol groups, dithiocarboxyl groups, sulfinyl groups, sulfonyl groups, sulfo groups, nitro groups, sulfide groups, disulfide groups, amino groups, primary amino groups, secondary amino groups, Si(OH)3, Ge(OH)3, Sn(OH)3, Si(SH)4, Ge(SH)4, Sn(SH)4, phosphate groups, AsO3 Examples of the nitrogen atom constituting an aromatic ring include H, AsOH, P(SH), As(SH), CH(SH), C(SH), CH(NH), C(NH), CH(OH), C(OH), CH(CN), C(CN), CH(RSH), C(RSH), CH(RNH), C(RNH), CH(ROH), C(ROH), CH(RCN), C(RCN), and nitrogen atoms constituting an aromatic ring. In the above chemical formula, R represents an alkyl group or an aryl group having C1 to C5. The nitrogen atom constituting an aromatic ring means a nitrogen atom in a ring such as pyridine, pyrimidine, pyridazine, pyrazine, triazine, imidazole, thiazole, oxazole, phenanthroline, quinoline, isoquinoline, naphthyridine, purine, bipyridine, and terpyridine. The functional group contained in the organic ligand is not particularly limited, but examples thereof include an alkenyl group, an alkynyl group, an amino group, a carboxyl group, a glycidyl group, an isocyanate group, a hydroxyl group, and a thiol group.
[0023] The monomer constituting the polymer chain in the polymer gel is not particularly limited as long as it is capable of synthesizing a gel such as a hydrogel and is capable of reacting with a functional group introduced into the metal-organic framework. For example, (meth)acrylic acid, sodium (meth)acrylate, potassium (meth)acrylate, lithium (meth)acrylate, vinyl benzoic acid, sodium vinyl benzoate, potassium vinyl benzoate, lithium vinyl benzoate, vinyl acetic acid, sodium vinyl acetate, potassium vinyl acetate, lithium vinyl acetate, vinyl sulfonic acid, sodium vinyl sulfonate, potassium vinyl sulfonate Examples of the monomers include acrylic acid, lithium vinyl sulfonate, p-styrene sulfonic acid, sodium p-styrene sulfonate, potassium p-styrene sulfonate, lithium p-styrene sulfonate, allyl sulfonic acid, sodium allyl sulfonate, potassium allyl sulfonate, lithium allyl sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, sodium 2-acrylamido-2-methylpropanesulfonate, potassium 2-acrylamido-2-methylpropanesulfonate, lithium 2-acrylamido-2-methylpropanesulfonate, (meth)acrylic acid esters, etc. In addition, when a vinyl acetate-based monomer is used, saponification may be performed after the polymerization reaction. In addition, the above-mentioned monomers may be used alone or in combination. In addition, other monomers may be copolymerized within a range that does not impair the gist of the present invention.
[0024] The liquid constituting the polymer gel is not particularly limited, but examples thereof include water, organic solvents, etc. The liquid may contain a solute such as a salt dissolved therein, as long as the purpose of the present invention is not impaired.
[0025] The amount of the metal organic framework relative to the polymer in the polymer gel may be an amount necessary for the polymer to gel and release a target amount of chemical species, and is preferably 5% by weight or more, more preferably 10% by weight or more, even more preferably 20% by weight or more, and particularly preferably 30% by weight or more.
[0026] <Method of manufacturing polymer gel> The polymer gel according to the embodiment of the present invention can be manufactured, for example, through a functional group introduction step and a gelation step. In the functional group introduction step, a first functional group-containing metal organic framework is prepared by introducing a plurality of first functional groups into the metal organic framework. In the gelation step, the second functional group of a polymer having a plurality of second functional groups capable of reacting with the first functional group is reacted with the first functional group to form a covalent bond, thereby obtaining a polymer gel. The polymer having a plurality of second functional groups may be a homopolymer or a copolymer.
[0027] When the first functional group is an amino group or a hydroxyl group, the second functional group is, for example, a carboxyl group, and when the first functional group is a carboxyl group, the second functional group is, for example, an amino group or a hydroxyl group.
[0028] In another method for producing a polymer gel, the polymer gel may be obtained by polymerizing a monomer having a second functional group capable of undergoing a polymerization reaction with the first functional group and a metal organic framework having the first functional group in the gelation step.
[0029] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. EXAMPLES
[0030] 1. Synthesis of MOF cross-linked polymer gel (1) Synthesis of Metal-Organic Frameworks 0.279g (0.936mmol) of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 0.253g (0.936mmol) of azobenzene-4,4'-dicarboxylic acid (hereinafter sometimes referred to as "AzDC"), and 0.085g (0.466mmol) of 1,2-bis(4-pyridyl)ethylene (hereinafter sometimes referred to as "BPE") were dissolved in 100mL of dimethylformamide (hereinafter sometimes referred to as "DMF"), and the solution was heated to 100℃ and stirred for 11 hours to obtain block-shaped red crystals. The obtained red crystals were washed with 100mL of DMF and 100mL of hexane, and the washed red crystals were then distilled under reduced pressure to obtain the target metal-organic framework, Zn(AzDC)(BPE). 0.5 The synthesis scheme is shown in the following chemical reaction formula (A).
[0031] [ka]
[0032] (2) Introduction of amino groups into metal-organic frameworks 5.8 mg (0.075 mmol) of aminoethanethiol was dissolved in 20 mL of ultrapure water. Then, 100 mg of Zn(AzDC)(BPE) was added to the aminoethanethiol aqueous solution. 0.5 After adding, the solution was stirred for 1 hour. The solution was then dialyzed against ultrapure water using a cellulose dialysis membrane (molecular weight cutoff: 1000) for 3 days. The external dialysis solution was exchanged 9 times. After dialysis, the solvent was removed from the solution by vacuum distillation, and the solution was freeze-dried to obtain the target Zn(AzDC)(BPE). 0.5 The synthesis scheme is shown in the following chemical reaction formula (B).
[0033] [ka]
[0034] (3) Synthesis of polymethacrylic acid 5 g (58.1 mmol) of methacrylic acid from which the polymerization inhibitor had been removed using an alumina column and 94 mg (0.29 mmol) of 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride (water-soluble azo polymerization initiator VA-044 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 5 mL of degassed ultrapure water. Then, the aqueous solution was shaken at 60°C for 1 hour under a nitrogen atmosphere to obtain a white solid. The obtained white solid was dissolved in 40 mL of ultrapure water. Then, the aqueous solution was dialyzed with ultrapure water for 1 day using a cellulose dialysis membrane (molecular weight cutoff 3500 Da). At this time, the external solution for dialysis was exchanged three times. After the dialysis, the aqueous solution was freeze-dried to obtain the target polymethacrylic acid. The synthesis scheme is as shown in the following chemical reaction formula (C).
[0035] [ka]
[0036] (4) Encapsulation of carbon dioxide into metal-organic frameworks Zn(AzDC)(BPE) 0.5 -NH2 was vacuum dried to obtain Zn(AzDC)(BPE). 0.5 After removing the internal gas and solution, Zn(AzDC)(BPE) 0.5 -NH2 is supplied with carbon dioxide to produce Zn(AzDC)(BPE) 0.5 Carbon dioxide was encapsulated in the
[0037] (5) Synthesis of MOF cross-linked polymer gel 50 mg (0.581 mmol) of polymethacrylic acid (hereinafter sometimes referred to as "PMAc") was dissolved in 400 μL of ultrapure water, and the pH of the PMAc aqueous solution was adjusted to pH 7-8 with solid sodium hydroxide. Next, to the pH-adjusted PMAc aqueous solution, 22.27 mg (0.1162 mmol) of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (hereinafter sometimes referred to as "EDC") was dissolved in 50 μL of ultrapure water to form an EDC aqueous solution, and 13.37 mg (0.1162 mmol) of N-hydroxysuccinimide (hereinafter sometimes referred to as "NHS") was dissolved in 50 μL of ultrapure water to form an NHS aqueous solution. Next, 20 mg of Zn(AzDC)(BPE) was added to the PMAc aqueous solution to which the EDC aqueous solution and the NHS aqueous solution had been added. 0.5 -NH2 (carbon dioxide already enclosed) was added and stirred until it was sufficiently dispersed in the aqueous solution, and the dispersion was then allowed to stand to obtain the desired MOF crosslinked polymer gel. The synthesis scheme is shown in the following chemical reaction formula (D).
[0038] [ka]
[0039] 2. Zn(AzDC)(BPE) 0.5 and physical properties of MOF crosslinked polymer gels (1) Zn(AzDC)(BPE) 0.5 Confirmation of carbon dioxide adsorption and desorption behavior Zn(AzDC)(BPE) was measured using a high pressure gas adsorption measurement device (BELSORP HP manufactured by Microtrack-Bel Co., Ltd.). 0.5 The carbon dioxide adsorption and desorption behavior of 250 mg of Zn(AzDC)(BPE) 0.5 After drying in a vacuum, the adsorption temperature was set to 298K and the saturated vapor pressure was set to 6444.8kPa. Zn(AzDC)(BPE) was adsorbed with carbon dioxide while changing the pressure from 0kPa to 220kPa. 0.5 The carbon dioxide adsorption amount (mg / g) was measured.
[0040] As shown in Figure 1, Zn(AzDC)(BPE) 0.5 It was revealed that the amount of carbon dioxide (CO2) adsorbed increased as the pressure increased, and the amount of carbon dioxide adsorbed decreased as the pressure decreased. 0.5 As the pressure increases, it adsorbs more carbon dioxide (CO2), and as the pressure decreases, it releases more carbon dioxide. As is clear from Figure 1, the amount of carbon dioxide adsorbed when the pressure is decreased is slightly greater than the amount of carbon dioxide adsorbed when the pressure is increased, but the adsorption and desorption of carbon dioxide can be said to be almost reversible.
[0041] (2) Viscoelasticity evaluation of polymer gels The viscoelastic properties of the MOF cross-linked polymer gel were measured using a Modular Compact Rheometer manufactured by Anton Paar. Specifically, the MOF cross-linked polymer gel was synthesized on the bottom side of a sample tube using the above-mentioned MOF cross-linked polymer gel synthesis method, and then the MOF cross-linked polymer gel was removed from the sample tube and cut to fit an 8 mm parallel plate to prepare a sample piece. The sample piece was then set together with the parallel plate in the Modular Compact Rheometer, and its viscoelastic properties were measured at a measurement temperature of 25°C.
[0042] As shown in Figure 2, when the viscoelastic properties of the MOF cross-linked polymer gel according to the present invention were measured, the storage modulus was greater than the loss modulus, indicating that the MOF cross-linked polymer gel was sufficiently gelled.
[0043] (3) Zn(AzDC)(BPE) 0.5 Effect of compressive load on carbon dioxide release from MOF crosslinked polymer gels After synthesizing MOF cross-linked polymer gel on the bottom side of each of the three sample tubes using the above-mentioned MOF cross-linked polymer gel synthesis method, the same concentration of barium hydroxide aqueous solution was added to each of the sample tubes. Next, a 100g weight was placed in one sample tube, a 200g weight was placed in another sample tube (see Figure 3), and no weight was placed in the remaining sample tubes. 30 seconds after the weights were added, pH titration was performed with hydrochloric acid on the barium hydroxide aqueous solution in all three sample tubes to determine the amount of carbon dioxide released (when carbon dioxide dissolves in the barium hydroxide aqueous solution, a neutralization reaction shown by Ba(OH)2+CO2→BaCO3↓+H2O occurs, and the hydroxyl ions (OH - ) are consumed. Here, the amount of carbon dioxide released is calculated by calculating the amount of hydroxyl ions consumed. ) The results were plotted as a graph, and the graph shown in FIG. 4 was obtained. As is clear from the graph in FIG. 4, the more compressive load is applied to the MOF cross-linked polymer gel of this example, the more the Zn(AzDC)(BPE) in the MOF cross-linked polymer gel increases. 0.5 It was found that the amount of carbon dioxide released from the derived unit increased. The presence of carbon dioxide was also observed in the system without the weight, but this is thought to be due to carbon dioxide in the air dissolving into the barium hydroxide solution.
[0044] Comparative Example 1 1. Synthesis of polymer gel (1) Synthesis of polymethacrylic acid Polymethacrylic acid was obtained by the same method as that described in the section "(3) Synthesis of polymethacrylic acid" of "1. Synthesis of polymer gel" in Example 1.
[0045] (2) Synthesis of polymer gel 75 mg (0.872 mmol) of PMAc was dissolved in 400 μL of ultrapure water, and then 16 μL (0.261 mmol) of ethylenediamine and an EDC aqueous solution prepared by dissolving 50.15 mg (0.2615 mmol) of EDC in 50 μL of ultrapure water were added to the PMAc aqueous solution. The PMAc aqueous solution was stirred and then allowed to stand to obtain the desired polymer gel.
[0046] (Comparison of physical properties between MOF crosslinked polymer gel according to Example 1 and polymer gel according to Comparative Example 1) 1. Carbon dioxide release behavior under compressive load A solution (45.4 μM, 3 mL) of Basic Red 5 [absorbance: 0.500 or more (10 mg / L, pH 6.4, 523.0-527.0 nm) (dry matter equivalent)] was poured into a prismatic cell for measurement, and the prismatic cell was set in a spectrophotometer (UV-1800 manufactured by Shimadzu Corporation) to measure the absorbance of the Basic Red 5 solution at 527 nm. Next, using the synthesis method of the polymer gel shown in Example 1 and Comparative Example 1, a polymer gel was formed on the bottom side of each of the two prismatic cells for the compression deformation test, and then the Basic Red 5 solution whose absorbance had been measured earlier was poured from above each prismatic cell. Then, as shown in FIG. 5, a glass rod was inserted from above the prismatic cell, and the polymer gel was compressed and deformed with the glass rod (first compression deformation). Thereafter, the glass rod was removed from the prismatic cell, and the Basic Red 5 aqueous solution was poured into the measurement prismatic cell. The cell was then set in the above-mentioned spectrophotometer to measure the absorbance of the Basic Red 5 aqueous solution at 527 nm, and the difference from the initially measured absorbance was calculated to determine the amount of absorbance change.
[0047] Next, the same operation as above was performed on each polymer gel (second compressive deformation), and then the prismatic cell was set in the spectrophotometer as above to measure the absorbance of the Basic Red 5 aqueous solution at 527 nm. The difference from the absorbance measured during the first compressive deformation was calculated and used as the change in absorbance.
[0048] Next, the same operation as above was performed on each polymer gel (third compressive deformation), and then the prismatic cell was set in the spectrophotometer as above to measure the absorbance of the Basic Red 5 aqueous solution at 527 nm. The difference from the absorbance measured during the second compressive deformation was calculated and used as the change in absorbance.
[0049] FIG. 6 shows histograms of the absorbance change of the Basic Red 5 aqueous solution versus the number of compressions for the MOF crosslinked polymer gel according to Example 1 and the polymer gel according to Comparative Example 1. As is clear from FIG. 6, for the polymer gel according to Comparative Example 1, the absorbance change of the Basic Red 5 aqueous solution was almost constant regardless of the number of compressions, but for the MOF crosslinked polymer gel according to Example 1, the absorbance change of the Basic Red 5 aqueous solution increased as the number of compressions increased. This indicates that nothing is released from the inside of the polymer gel according to Comparative Example 1 when it is compressed, but carbon dioxide is released from the inside of the MOF crosslinked polymer gel according to Example 1 when it is compressed (it is presumed that the pH is reduced by dissolving carbon dioxide in the Basic Red 5 aqueous solution, the redness of the Basic Red 5 aqueous solution increases, and the absorbance of the Basic Red 5 aqueous solution increases).
[0050] 2. Effect of compressive stress on carbon dioxide release A petri dish was set on a compression tester equipped with a load cell, and the MOF cross-linked polymer gel prepared in Example 1 was placed on it. Then, a basic red 5 aqueous solution (45.4 μM, 500 μL) was added to the petri dish so that the MOF cross-linked polymer gel was immersed, and the electrodes of the pH meter were brought into contact with the basic red 5 aqueous solution. After the pH value indicated by the pH meter stabilized to a certain extent, the pH value was measured while gradually applying a compressive stress to the MOF cross-linked polymer gel. The same measurement was also performed on the polymer gel prepared in Comparative Example 1. The results are shown in FIG. 7. As is clear from FIG. 7, for the polymer gel according to Comparative Example 1, the amount of pH change rapidly increased until the compressive stress reached 10 Pa, but once it exceeded 10 Pa, the amount of pH change rapidly decreased and increased slightly, and once the compressive stress exceeded 50 Pa, the amount of pH change increased very slightly or became almost constant. On the other hand, for the MOF cross-linked polymer gel according to Example 1, the amount of pH change rapidly increased until the compressive stress reached 10 Pa, and then continued to increase steadily, although the increase in the amount of increase became smaller as the compressive stress increased. 7, the amount of pH change remains the same for both polymer gels until the compressive stress reaches 10 Pa, but once the compressive stress exceeds 10 Pa, the difference between the amount of pH change for both gels increases the higher the compressive stress. This indicates that nothing is released from the inside of the polymer gel according to Comparative Example 1 when it is compressed, but carbon dioxide is released from the inside of the MOF cross-linked polymer gel according to Example 1 when it is compressed (in the polymer gel according to Comparative Example 1, a change in pH is observed until the compressive stress exceeds 10 Pa, which is presumably due to the release of protons from the carboxylic acid in the polymer gel). [Industrial Applicability]
[0051] The method for releasing chemical species encapsulated in a metal organic framework according to the present invention is a novel method that has never been proposed before, and can be applied to, for example, the release of drugs for treating moving parts such as joints, molecular actuators that operate due to the release of chemical species, separation materials for two or more chemical species, control of cell behavior, etc.
Claims
1. A mechanical external force (excluding external force load due to reduced pressure) is applied to a polymer gel with crosslinking points of metal-organic frameworks that encapsulate chemical species. ) to release the chemical species outside the metal-organic framework.
2. The metal-organic framework is covalently bonded as a crosslinking point. The metal organic framework encapsulates a chemical species, Mechanical external force (excluding external load due to reduced pressure) ) is added to the polymer gel, thereby releasing the chemical species to the outside of the metal-organic framework.
3. a functional group introduction step of introducing a plurality of first functional groups into the metal-organic framework to prepare a first functional group-containing metal-organic framework; a chemical species-containing step of preparing a chemical species-containing first functional group-containing metal-organic framework by including a chemical species in the first functional group-containing metal-organic framework; a gelation step of reacting a second functional group of a polymer having a plurality of second functional groups capable of reacting with the first functional group of the chemical species-encapsulating first functional group-containing metal-organic framework with the first functional group to form a covalent bond therebetween, thereby obtaining a polymer gel; The method for producing a polymer gel comprises the steps of:
Citation Information
Patent Citations
Adsorbent for gas
JP1980027028A
Polymer complex, and gas adsorbing material and gas separation apparatus using the same
JP2012246438A
Gas separation method
JP2015529550A
PCP complex
WO2015012373A1